Analysis of soil bacterial communities and physicochemical properties associated with Fusarium wilt disease of banana in Malaysia - Jamil, Fatin Nadiah; Mohd Hashim, Amalia; Yusof, Mohd Termizi; Saidi, Noor Baity (Nature Publishing Group, 2022)
Fusarium wilt (FW) caused by Fusarium oxysporum f. sp. cubense Tropical Race 4 (TR4) is a soil-borne disease that infects bananas, causing severe economic losses worldwide. To reveal the relationship between bacterial populations and FW, the bacterial communities of healthy and TR4-infected rhizosphere and bulk soils were compared using 16S rRNA gene sequencing. Soil physicochemical properties associated with FW were also analyzed. We found the community structure of bacteria in the healthy and TR4 infected rhizosphere was significantly different compared to bulk soil within the same farm. The rhizosphere soils of infected plants exhibited higher richness and diversity than healthy plant with significant abundance of Proteobacteria. In the healthy rhizosphere soil, beneficial bacteria such as Burkholderia and Streptomyces spp. were more abundant. Compared to the infected rhizosphere soil, healthy rhizosphere soil was associated with RNA metabolism and transporters pathways and a high level of magnesium and cation exchange capacity. Overall, we reported changes in the key taxa of rhizospheric bacterial communities and soil physicochemical properties of healthy and FW-infected plants, suggesting their potential role as indicators for plant health.